A beam‐column element for modeling nonlinear flexural and shear behaviors of reinforced masonry walls. (1st April 2022) - Cheng, Jianyu; Shing, P. Benson
Abstract: This paper presents a computationally efficient beam‐column element to simulate the nonlinear flexural and shear behaviors of reinforced masonry shear walls subjected to bilateral seismic forces. A three‐field mixed formulation based on the Hu‐Washizu variational principle is adopted. This mixed element is free of shear locking, and allows a wall to be modeled with one element. The axial and flexural responses are evaluated with a fiber‐section model at each integration point along the element, while the shear response in each loading direction is represented by a phenomenological model. The element accounts for the influence of the axial load, wall aspect ratio, and wall flange, if any, on the shear response of a wall. To consider axial‐flexure‐shear interaction, the shear model takes into account the axial stress resultant from the fiber‐section model, and the compressive strength of masonry in the fiber‐section model decreases when severe shear damage developed. The model has been calibrated and validated with experiment data. It has been demonstrated that it is able to reproduce experimental results from quasi‐static cyclic loading tests of single walls as well as shake‐table tests of wall systems with good accuracy. Furthermore, the ability of the proposed model to simulate the response of reinforced masonry shear wall systems subjected to bilateral seismic forces has been examined by comparing with results from a detailed finite element model.